Xylapeptide A, an Antibacterial Cyclopentapeptide with an Uncommon L-Pipecolinic Acid Moiety from the Associated Fungus Xylaria sp. (GDG-102) - Wei-Feng Xu (Nature Portfolio, 2017)
Abstract Two new cyclopentapeptides, xylapeptide A (1) with an uncommon L-pipecolinic acid moiety, and xylapeptide B (2) having a common L-proline residue were identified from an associated fungus Xylaria sp. isolated from the Chinese medicinal plant Sophora tonkinensis. Their planar structures were elucidated by a comprehensive analysis of NMR and MS spectroscopic spectra. The absolute configurations were determined by Marfey’s method and single-crystal X-ray diffraction (Cu Kα) analysis. Xylapeptide A (1) is the first example of cyclopentapeptide with L-Pip of terrestrial origin and showed strong antibacterial activity against Bacillus subtilis and B. cereus with MIC value of 12.5 μg/mL.